The perfect mother : a novel - Molloy, Aimee (New York, NY : Harper, 2018)
"They call themselves the May Mothers$1 (Ba group of new moms whose babies were born in the same month. Twice a week, they get together in Brooklyn$1 (Bs Prospect Park for some much-needed adult time.When the women go out for drinks at the hip neighborhood bar, they are looking for a fun break from their daily routine. But on this hot Fourth of July night, something goes terrifyingly wrong: one of the babies is taken from his crib. Winnie, a single mom, was reluctant to leave six-week-old Midas with a babysitter, but her fellow May Mothers insisted everything would be fine. Now he is missing. What follows is a heart-pounding race to find Midas, during which secrets are exposed, marriages are tested, and friendships are destroyed."--s
Keywords: Female friendship -- Fiction; Single mothers -- Fiction; Kidnapping -- Fiction; Brooklyn (New York, N.Y.) -- Fiction; Psychological fiction; Thrillers (Fiction)